Digital transformation in South African consumer packaged goods companies - Ngaleka, Tshepo (Graduate School of Business (GSB), 2026)
Technology-driven consumer expectations and increasing market competition are compelling Consumer Packaged Goods (CPG) companies to integrate digital technologies into their processes and systems to remain competitive and thrive in the market. However, little is known about how digital technologies affects job losses, employee interactions, organizational strategies and digital transformation strategies in South African CPG companies. This study addresses these gaps by exploring three research questions using the theoretical frameworks, namely Resource Based View, Dynamic Capabilities View and Digital Business Ecosystem to understand the intricacies of digital transformation in the CPG industry in South Africa. The study employed a qualitative research approach and semi-structured interviews were used to obtain data from 20 industry professionals. The main findings showed that digital transformation changed employee roles and responsibilities over time, creating opportunities and challenges. It was also established that the adoption of digital transformation varied as some organizations employed inclusive practices that fostered cooperation and innovation, while others focused on efficiency and increasing productivity. Regardless of the approach, it was evident that excellent leadership based on communication and transparency was found as a crucial feature for successful digital transformation initiatives undertaken by these companies as it boosted employee morale and increased commitment to these initiatives.